Gene deletion in an Italian haemophilia B subject. Issue 4 (August 1985) - Bernardi, F; del Senno, L; Barbieri, R; Buzzoni, D; Gambari, R; Marchetti, G; Conconi, F; Panicucci, F; Positano, M; Pitruzzello, S
Abstract : DNA from 20 Italian haemophilia B patients was analysed by the Southern blotting technique and hybridisation to a factor IX cDNA probe. A large deletion of factor IX gene was detected in one patient with antibodies to the infused factor; the EcoRI pattern of the other 19 subjects examined was normal.